2020
DOI: 10.1089/apc.2020.0074
|View full text |Cite
|
Sign up to set email alerts
|

Is Patient Navigation Used by People with HIV Who Need It? An Assessment from the Medical Monitoring Project, 2015 − 2017

Abstract: We (1) estimated the prevalence of not getting patient navigation despite feeling a need for the service (unmet subjective need) or despite having unsuppressed viral load (unmet objective need) among people with HIV (PWH), (2) determined reasons why PWH did not use the service, and (3) determined factors associated with unmet need for patient navigation. We used combined data from the 2015 to 2017 cycles of the Medical Monitoring Project, an HIV surveillance system designed to produce nationally representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…However, there are challenges associated with creating awareness of HIV CHOs and PN programmes across the broader primary care sector. As the number of non‐s100 specialist GPs diagnosing PLHIV continues to increase (Kirby Institute, 2017; Newman et al., 2015), there is an urgent need to foster awareness of and referral pathways to HIV CHOs as essential resources supporting the care of PLHIV (Mizuno et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are challenges associated with creating awareness of HIV CHOs and PN programmes across the broader primary care sector. As the number of non‐s100 specialist GPs diagnosing PLHIV continues to increase (Kirby Institute, 2017; Newman et al., 2015), there is an urgent need to foster awareness of and referral pathways to HIV CHOs as essential resources supporting the care of PLHIV (Mizuno et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although PLWH experiencing homelessness may have access to Ryan White HIV/AIDS program services (Doshi et al, 2017), a large proportion may have unmet needs for behavioral health services, dental care, access to transportation, and housing services (Dray-Spira et al, 2012; Padilla et al, 2020; Wainwright et al, 2020). Interventions to alleviate unmet needs and improve HIV outcomes, such as intensive case management, patient navigators, and financial incentives, have been initiated in a variety of venues (Clemenzi-Allen et al, 2020; Mizuno et al, 2020; Rajabiun et al, 2018; Sarango et al, 2017). These interventions could benefit people who are unstably housed and who may be potentially at risk for literal homelessness.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting navigation services to clients with high anxiety is essential to ensuring that those with the biggest need are reached, as research in the United States has found that over a third of PLHIV did not use health navigation despite having a need for it. 39 Although our findings suggest that navigation interventions may have a positive impact on anxiety among GBMSM living with HIV, many interactions between a navigator and patient were needed to see a significant effect. This may be cost-prohibitive in some settings.…”
Section: Discussionmentioning
confidence: 62%